Research Directions of SMEs and Entrepreneurship in Conditions of Socio-Economic Change. Selected Issues - Anna DĘBICKA; Karolina OLEJNICZAK (Communications of International Proceedings, 2021)
The article attempts to identify emerging research areas on entrepreneurship and small and medium-sized enterprises that may increase in importance. Based on the analysis of recent events triggered by Covid-19, possible directions of SMEs and entrepreneurship research in the context of socio-economic changes have been suggested. The paper is intended to be a literature review of crises management and its importance from the perspective of small and medium-sized enterprises. Further, a literature review of the human factor from the new entrepreneurship framework's perspective was presented. Finally, conclusions regarding these aspects were formulated, and further research areas were indicted.
Keywords: Entrepreneurship; SMEs; Crisis Management; Humane Entrepreneurship